Conceptual View of the Mechanism of Innovative Development by the Level in the Economy - Kurbatov, Vladimir L.; Naumenko, Svetlana M.; Halina, Maria V. (International Review of Management and Marketing, 2016)
Implementation mechanism of innovative development is a very important task of modern economic theory and practice, the solution of which will allow in the long term competitiveness of the country by increasing its advantage in science, education and high technologies in the economic, scientific-technical and other fields. This article deals with some aspects of the mechanism of innovation development at the micro, macro - and meso - levels of the economy, describes the innovative company which is characterized by high-tech capabilities. The principles of managing the mechanism of innovative development at the micro level are the comparative characteristic of high-tech enterprises and traditional industries. This area is also complemented by the consideration of the main provisions of the control mechanism of innovation development at the meso level. Stand and describes specific areas of the mechanism of innovation development in the framework of macroeconomic models and the main provisions of the “triple helix”. Keywords: innovative development, mechanism innovation firm, high-tech industry JEL Classifications: L60, O3